Crystallization and preliminary X‐ray diffraction analysis of the phosphate‐binding protein PhoX from Xanthomonas citri. Issue 12 (1st December 2014) - Pegos, Vanessa R.; Medrano, Francisco Javier; Balan, Andrea
<x xml:space="preserve">Abstract</x> Xanthomonas axonopodis pv. citri (X. citri) is an important bacterium that causes citrus canker disease in plants in Brazil and around the world, leading to significant economic losses. Determination of the physiology and mechanisms of pathogenesis of this bacterium is an important step in the development of strategies for its containment. Phosphate is an essential ion in all microrganisms owing its importance during the synthesis of macromolecules and in gene and protein regulation. Interestingly, X. citri has been identified to present two periplasmic binding proteins that have not been further characterized: PstS, from an ATP‐binding cassette for high‐affinity uptake and transport of phosphate, and PhoX, which is encoded by an operon that also contains a putative porin for the transport of phosphate. Here, the expression, purification and crystallization of the phosphate‐binding protein PhoX and X‐ray data collection at 3.0 Å resolution are described. Biochemical, biophysical and structural data for this protein will be helpful in the elucidation of its function in phosphate uptake and the physiology of the bacterium.